Structural Volatility in Chile: A Policy Report - Ricardo J. Caballero (Inter-American Development Bank, Research Department, 2000)
This paper identifies Chile`s economic weaknesses and offers policy recommendations for increasing stability. Current problems include weak international financial links, a Central Bank mandate that is ill-designed to deal with terms of trade shocks, a propensity to waste scarce liquidity in the banking system; and limited development of financial markets. The paper`s policy recommendations include improving external financial links, molding terms of trade contingencies into anti-cyclical policies, Improving liquidity aggregation through and within the banking sector during crises, and improving the liquidity and immediacy of domestic financial instruments.
Keywords: 330; Volatilität; Wirtschaftswachstum; Erwerbstätigkeit; Internationaler Finanzmarkt; Internationale Finanzierung; Finanzpolitik; Terms of Trade; Geldpolitik; Liquidität; Chile